Cinder & Glass - De la Cruz, Melissa, 1971- (New York : G.P. Putnam's Sons, 2022)
"The king sends out an invitation to all the maidens in France: their presence is requested at a number of balls and events that will be held in honor of the dashing Prince Louis, who must choose a bride. Cendrillon de Louvois has more grace, beauty, and charm than anyone else in France. While she was once the darling child of the king's favorite adviser, her father's death has turned her into the servant of her stepmother and cruel stepsisters--and at her own chateau, too! Cendrillon--now called Cinder--manages to evade her stepmother and attend the ball, where she catches the eye of the handsome Prince Louis and his younger brother Auguste. Even though Cendrillon has an immediate aversion to Louis, and a connection with Auguste, the only way to escape her stepmother is to compete with the other women at court for the Prince's hand. Soon, as Cendrillon grows closer to Auguste and dislikes the prince more and more, she will have to decide if she can bear losing the boy she loves in order to leave a life she hates."--
Keywords: Cinderella (Legendary character) -- Juvenile fiction; Cinderella (Legendary character) -- Fiction; Princesses -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Love -- Juvenile fiction; Fairy tales -- Juvenile fiction; Folklore -- Juvenile fiction. -- France; Princesses -- Fiction; Interpersonal relations -- Fiction; Love -- Fiction; Fairy tales -- Fiction; Folklore -- Fiction. -- France; Versailles (France) -- Juvenile fiction; Fantasy; Versailles (France) -- Fiction; Fantasy fiction; Fairy tales